Experimental Assessment of Vulnerability to Warming in Tropical Shallow-Water Marine Organisms - Yucharoen, Mathinee; Sinutok, Sutinee; Chotikarn, Ponlachart; Buapet, Pimchanok (Frontiers in Marine Science, 2021)
Tropical shallow-water habitats represent the marine environments with the greatest biodiversity; however, these habitats are the most vulnerable to climate warming. Corals, seagrasses, and macroalgae play a crucial role in the structure, functions, and processes of the coastal ecosystems. Understanding their growth and physiological responses to elevated temperature and interspecific sensitivity is a necessary step to predict the fate of future coastal community. Six species representatives, including Pocillopora acuta, Porites lutea, Halophila ovalis, Thalassia hemprichii, Padina boryana, and Ulva intestinalis, collected from Phuket, Thailand, were subjected to stress manipulation for 5 days. Corals were tested at 27℃, 29.5℃, 32℃, and 34.5℃, while seagrasses and macroalgae were tested at 27℃, 32℃, 37℃, and 42℃. After the stress period, the species were allowed to recover for 5 days at 27℃ for corals and 32℃ for seagrasses and macroalgae. Non-destructive evaluation of photosynthetic parameters (Fv/Fm, Fv/F0, PSII, NPQ and rapid light curves) was carried out on days 0, 3, 5, 6, 8 and 10. Chlorophyll contents and growth rates were quantified at the end of stress, and recovery periods. An integrated biomarker response (IBR) approach was adopted to integrate the candidate responses (Fv/Fm, chlorophyll content, and growth rate) and quantify the overall temperature effects. Elevated temperatures were found to affect photosynthesis, chlorophyll content, and growth rates of all species. Lethal effects were detected at 34.5℃ in corals, whereas adverse but recoverable effects were detected at 32℃. Seagrasses and macroalgae displayed a rapid decline in photosynthesis and lethal effects at 42℃. In some species, sublethal stress manifested as slower growth and lower chlorophyll content at 37℃, while photosynthesis remained unaffected. Among all, T. hemprichii displayed the highest thermotolerance. IBR provided evidence that elevated temperature affected the overall performance of all tested species, depending on temperature level. Our findings show a sensitivity that differs among important groups of tropical marine organisms inhabiting the same shallow-water environments and highlights the importance of integrating biomarkers across biological levels to assess their vulnerability to climate warming.